First Report of Natural Infection of Phlebotomus mongolensis to Leishmania major and Leishmania turanica in the Endemic Foci of Zoonotic Cutaneous Leishmaniasis in Iran - Azad Absavaran; Mehdi Mohebali; Vahideh Moin-Vaziri; Alireza Zahraei-Ramazani; Amir Ahmad Akhavan; Sayena Rafizadeh; Amirhossein Rassi; Alireza Barmaki; Yavar Rassi (Tehran University of Medical Sciences, 2023)
Background: The primary aim of this study is to determine infection to Leishmania parasites in the wild population of Phlebotomus caucasicus and Phlebotomus mongolensis using molecular methods in some important zoonotic cutaneous leishmaniasis foci in Iran. Methods: Sand flies were collected from active colonies of rodent burrows from 16 trapping sites using sticky trap paper. In order to detect and identify of Leishmania parasites in females Ph. caucasicus and Ph. mongolensis, the Nested-PCR amplification of ITS2-rDNA region was performed to generate amplicon with 245bp for Leishmania major, 206bp for L. gerbilli and 141bp for L. turanica. Results: In the current study we found DNA of different gerbil parasites such as L. major and L. turanica, and mixed infection of L. major/L. turanica in Ph. caucasicus and Ph. mongolensis. It should be noted that, in Iran, natural infection with Leishmania parasites is recorded for the first time in this study in Ph. mongolensis. Conclusion: Both species of Ph. caucasicus and Ph. mongolensis not only may participate in the ZCL transmission cycle between reservoir hosts, but also results of this study support the  role of these species as secondary vectors in the transmission of leishmaniasis to humans.